Ab Initio Studies of Discharge Mechanism of MnO2 in Deep-Cycled Rechargeable Zn/MnO2 Batteries. Issue 2 (5th February 2020) - Magar, Birendra Ale; Paudel, Nirajan; Lambert, Timothy N.; Vasiliev, Igor
Abstract : Rechargeable alkaline Zn/MnO2 batteries are an attractive solution for large-scale energy storage applications. Recently, Bi and Cu additives have been used to increase the cycle life and capacity of rechargeable Zn/MnO2 batteries, with an equivalent of the full two-electron capacity realized for many cycles, in the absence of zinc. However, the mechanism of the effect of Bi and Cu on the performance of rechargeable Zn/MnO2 batteries has not been investigated in detail. We apply first-principles density functional computational methods to study the discharge mechanisms of the unmodified and Bi/Cu-modified γ -MnO2 electrodes in rechargeable alkaline Zn/MnO2 batteries. Using the results of our calculations, we analyze the possible redox reaction pathways in the γ -MnO2 electrode and identify the electrochemical processes leading to the formation of irreversible discharge reaction products, such as hausmannite and hetaerolite. Our study demonstrates the possibility of formation of intermediate Bi-Mn and Cu-Mn oxides in deep-cycled Bi/Cu-modified MnO2 electrodes. The formation of intermediate Bi-Mn and Cu-Mn oxides could reduce the rate of accumulation of irreversible reaction products in the MnO2 electrode and improve the rechargeability and cyclability of Zn/MnO2 batteries.